أثر التسويق الرقمي على سلوك المستهلك" دارسة تطبيقية على مصرف التجاري فرع العزيزية (Comprehensive Journal of Science, 2025)
Digital marketing is considered one of the most important modern methods adopted by institutions to promote their products and services electronically, such as through the internet, social media, and email. Therefore, the researchers chose to address this topic in their research. The study problem focused on the impact of digital marketing on consumer behavior at the National Commercial Bank. The study aimed to clarify the concept of digital marketing and its effect on consumer behavior, and to identify the impact of the electronic services offered by the National Commercial Bank's Al-Aziziyah branch on consumer behavior.To achieve the study's objectives and answer its research question, the study employed a descriptive and analytical approach by developing a questionnaire to collect data from the study population. The data obtained from the distributed questionnaires was analyzed using statistical methods in SPSS software.The study concluded that there is a positive effect of digital marketing on consumer behavior at the National Commercial Bank, with a positive trend in consumer behavior towards the electronic products offered by the bank.